Carcass characteristics of feedlot-finished Zebu and Caracu cattle - Resende,Flávio Dutra de (2014)
This study analyzes the chemical carcass characteristics and carcass losses in 86 cattle, both castrated and non-castrated, with an average initial weight of 329 kg and an average age of approximately 20 months, including 12 Gyr, 20 Guzerat, 20 Nellore, and 20 Caracu among the herds selected for weight determination at 378 days of age, as well as 14 Nellore cattle that were not selected. The diet contained a roughage-to-concentrate ratio of 60:40 in terms of dry matter (DM), with 14.8% crude protein as a percentage of DM and corn silage as roughage. A completely randomized 5 × 2 factorial experimental design was used, including five breeds and two sex classes. The following values were determined: losses due to the trimming of commercial cuts and cooking; shear force; the temperature and pH of the meat; and the chemical composition of the Hankins and Howe section (HH section). The castrated animals exhibited greater losses from the front trimmings compared with the non-castrated cattle. There were no differences in the final pH values of the carcasses among the breeds, although the noncastrated animals exhibited higher values than the castrated ones, likely because non-castrated animals were more susceptible to stress. The final pH remained within the range considered optimal for all of the carcasses studied. No differences were observed in the shear force among the breeds or between the two sexes. When appropriately managed, zebu breeds are capable of producing tender meat, thus meeting the demands of the consumer market.